Penerapan Model Pembelajaran Project Based Learning Dalam Membuat Desain Hiasan Bordir Pada Mata Pelajaran Hiasan Busana Untuk Meningkatkan Hasil Belajar Siswa Kelas XI Di SMKN 1 Sooko - Listamona, Lila; Nahari, Inty; Nashikhah, Ma’rifatun (Faidatuna, 2024)
The objectives of this research include 1) To determine the application of the Project Based Learning model in making embroidery decoration designs in the fashion decoration subject to improve the learning outcomes of Class XI students at SMKN 1 Sooko. 2.) To determine the effectiveness of applying the Problem Based Learning model in creating embroidery decoration designs in the fashion decoration subject to improve the learning outcomes of Class XI students at SMKN 1 Sooko. This type of research is quantitative research with a pre-experimental design and a one shot case study model. This research was carried out at SMK Negeri 1 Sooko in class XI Design and the number of students was 22 people. The data collection method used is observation to determine the application of the Project Based Learning model to embroidery decoration designs, questionnaires to determine student learning responses and tests to determine the effectiveness of implementing learning models on student learning outcomes. The results of the research state that the application of the Project Based Learning learning model can be seen from the implementation of the Project Based Learning learning model in the design of embroidery decorations in the fashion decoration subject, obtaining an average score of 3.7 for teacher activities and an average score of 3.4 for student activities. Student learning outcomes on the cognitive test obtained an average score of 81.5 and the average score on the psychomotor test obtained an average score of 87.5. The overall average score of students' learning outcomes was 86.4, which was declared complete the Minimum Learning Standard. As many as 85% of students completed the Minimum Learning Standard and 15% did not completed.